The impact on nutrition of the intrahousehold distribution of power - Habiba Djebbari (Institute for the Study of Labor (IZA), 2005)
The distribution of income within the household is found to matter for the allocation of resources towards nutrition. Rural Mexican households do not pool income, nor do they attain a Pareto-efficient allocation of resources. In contrast to what is commonly done in the literature, I do not assume that only the head of household and his wife share the decision-making. In particular, I present a new test of the unitary model in the context of extended families, which acknowledges that any household member may participate to the decision-making as long as he or she earns some income. I find that a change in the number of income earners is associated with a change in food calorie consumption controlling for the change in household size and household income. Both the number and identities of income earners matter in the extended family. In particular, when a female household member starts earning income, food consumption increases substantively. When it is a male household member who starts earning income, it decreases substantively.
Keywords: I12; D13; I38; 330; nutrition; intrahousehold allocation; extended families